Construction Diagram and Process of Technological Operation of Leveler Equipped with Auger Work Member - Norov, Sobirjon Negmurodovich (RA Journal of Applied Research, 2022)
The article covers theoretical research on the use of levelers equipped with auger work members in the process of leveling longitudinal irregularities in the current leveling of sowing areas. This work supports the practical solution of using a screw working particle in the current field planning. Significance of the work – reducing traction resistance to soil movement up to 20% enables the tractor unit to work at higher speeds of translational motion, the latter contributes to increased productivity, improved planning quality and reduced cash costs per unit of work performed.